EFEKTIVITAS METODE ATQA TERHADAP PEMBELAJARAN TADABBUR QUR’AN DI PESANTREN QUR’AN AR-RAHMAN, MEGAMENDUNG, BOGOR - Fauzan M, Ahmad; Alghifari Slamet, Muh. Ubaidillah; Badruzzaman, Ahmad Dimyati (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2024)
This study evaluates the effectiveness of the ATQA (Academy Tadaabur Qur’an) method in learning Tadabbur Qur'an at the Ar-Rahman Qur'an Islamic Boarding School, Megamendung, Bogor. The research method uses a case study with directur, teadher, Islamic boarding school students as participants. Data was collected through classroom observations, interviews with teachers, and Tadabbur Qur'an comprehension tests. Data analysis was carried out qualitatively and quantitatively. The results show that the ATQA method is effective in increasing students' understanding of the Al-Qur'an, including the ability to study, reflect on, and question the verses of the Al-Qur'an. In addition, this method deepens their understanding of moral and spiritual values. In conclusion, the implementation of the ATQA method in learning Tadabbur Qur'an at the Ar-Rahman Qur'an Islamic Boarding School can increase the effectiveness of learning and appreciation of the teachings of the Qur'an. The practical implication is a recommendation to integrate the ATQA method in the Islamic boarding school curriculum as an effort to strengthen understanding and appreciation of the Al-Qur'an among Islamic students